Exploiting the bead injection LOV approach to carry out spectrophotometric assays in wine: application to the determination of iron - Vidigal, Susana S. M. P. (2012)
A sequential injection lab-on-valve (SI-LOV) system was used to develop a new methodology for the determination of iron in wine samples exploiting the bead injection (BI) concept for solid phase extraction and spectrophotometric measurement. Nitrilotriacetic Acid (NTA) Superflow resin was used to build the bead column of the flow through sensor. The iron (III) ions were retained by the bead column and react with SCN- producing an intense red colour. The change in absorbance was monitored spectrophotometrically on the optosensor at 480 nm. It was possible to achieve a linear range of 0.09-5.0 mg L-1 of iron, with low sample and reagent consumption; 500 mu L of sample, 15 mu mol of SCN-, and 9 mu mol of H2O2, per assay. The proposed method was successfully applied to the determination of iron in wine, with no previous treatment other than dilution, and to other food samples.